Ups and downs of the negative in secondary school how to leave the "ingalls" way of pedagogy? - Antelo, Estanislao; Abramowski, Ana Laura (Clinical Styles. The Journal on the vicissitudes of childhood, 1999)
In this article we try to name the cause that prevents the fully functioning of the class: the presence of the negative. Our hypothesis is that our current preoccupation of getting our students' interest and motivation is based on the idea that negative can be solved by means of some knowledge. In this way, a political problem becomes a problem related to knowledge. In our opinion, it is just the contrary. We have to dialogue with the conflict.